Associations of albumin and nutritional index factors with delirium in patients admitted to the cardiac intensive care unit - Kim, Tae Wan; Ko, Ryoung Eun; Na, Soo Jin; Chung, Chi Ryang; Choi, Ki Hong; Park, Chi-Min; Yang, Jeong Hoon (Frontiers in Cardiovascular Medicine, 2023)
Background: Limited data are available on the association of malnutrition with the occurrence of delirium in the cardiac intensive care unit (CICU). Thus, we aimed to analyze whether nutritional indices and their components can predict the development of delirium in CICU. Methods: We enrolled 2,783 patients admitted to the CICU of Samsung Medical Center for more than 24 hours between September 2012 and December 2018. We assessed the nutritional status at admission using three indices, the Prognostic Nutrition Index (PNI), the Geriatric Nutritional Risk Index (GNRI), and the Controlling Nutritional Status (CONUT). Then, we compared predictive performances for the occurrence of delirium among nutritional indices using Delong’s test. Results: Delirium developed in 678 patients (24.3%) assessed three times daily for seven days of CICU stay. Nutritional indices had fair predictive performance for development of delirium in critically ill cardiac patients using the area under the receiver-operating characteristic curve (AUROC: 0.729 for the GNRI, 0.728 for PNI, and 0.762 for CONUT). Furthermore, the AUROC of albumin alone (0.77, 95% CI, 0.75-0.79) was significantly greater than that of either GNRI (P < 0.001) or PNI (P < 0.001). In a multivariable analysis including each component of nutritional indices, albumin was a significant predictor for delirium but not absolute lymphocyte count, bodyweight/ideal bodyweight, or total cholesterol level as a component of nutritional indices. Conclusions: Predictive performances of nutritional indices for the occurrence of delirium were acceptable in patients admitted to CICU. Albumin alone might be a helpful and straightforward indicator for the occurrence of delirium.